Neglected and Underutilized Crop Species: The Key to Improving Dietary Diversity and Fighting Hunger and Malnutrition in Asia and the Pacific - Li, Xuan; Yadav, Rashmi; Siddique, Kadambot H. M. (Frontiers in Nutrition, 2020)
Asia continues to suffer from a high prevalence of malnutrition. Persistent malnutrition can be attributed to low dietary diversity, together with low production diversity. Dietary diversity represents a more healthy, balanced, and diverse diet, which ensures nutrient adequacy. The principle of dietary diversity is affirmed in all national food-based dietary guidelines. Food-based approaches that address malnutrition, especially micronutrient deficiencies, are embedded in evidence-based healthy diet patterns; however, they are disconnected from the current agricultural production system. Promising neglected and underutilized species (NUS) that are nutrient-dense, climate-resilient, profitable, and locally available/adaptable are fundamental to improving dietary and production diversity. The Future Smart Food Initiative, led by FAO's Regional Initiative on Zero Hunger, aims to harness the enormous benefits of NUS in the fight against hunger and malnutrition. Recognizing that NUS covers crops, livestock, fisheries and aquaculture, and forests, the FAO has set crops as an entry point for NUS to address hunger and malnutrition.